การใช้ภาษาบาลีสันสกฤตในภาษาไทย - ทองบ่อ, พระมหาสมศักดิ์ ธนปญฺโญ (วารสาร ศึกษาศาสตร์ มมร, 2018)
การศึกษาวิเคราะห์ครั้งนี้มีวัตถุประสงค์ เพื่อศึกษาวิเคราะห์ความเปลี่ยนแปลงภาษาบาลีสันสกฤตด้านรูปคำ เสียง และความหมายในภาษาไทย โดยเลือกภาษาทั้ง 2 ที่มีใช้ในภาษาไทยจำนวนภาษาละ 10 คำ รวม 20 คำด้วยวิธีการสุ่มตัวอย่างแบบจับสลาก เพื่อเป็นตัวอย่างในการวิเคราะห์ภาษาต่างประเทศในภาษาไทยสำหรับผู้สนใจสืบไป โดยใช้การเปรียบเทียบพจนานุกรม ฉบับราชบัณฑิตยสถาน 2542, กับหนังสือปทานุกรมบาลี ไทย อังกฤษ สันสกฤต ฉบับพระเจ้าบรมวงศ์เธอ กรมพระจันทบุรีนฤนาท ผลการวิเคราะห์ พบว่า 1. ภาษาบาลี เมื่อนำมาใช้ในภาษาไทยมีคงรูปคำไว้ตามแบบของบาลี 3 คำ แปลงคำหรือเพิ่มสัญลักษณ์ 7 คำ ด้านเสียงในภาษาบาลีกับภาษาไทยนั้นคงเสียงเดิม 6 คำ เปลี่ยนแปลงเสียง 4 คำ และ ด้านความหมายกว้างออก 8 คำ ความหมายย้ายที่ 2 คำ แต่ไม่พบความหมายแคบเข้า และความหมายคงเดิม 2. การศึกษาวิเคราะห์ความเปลี่ยนแปลงภาษาสันสกฤต เมื่อนำมาใช้ในภาษาไทยมีการคงรูป 1 คำ เปลี่ยนรูปคำเป็นอย่างอื่น 9 คำ ด้านเสียงในภาษาสันสกฤตกับภาษาไทยนั้นเปลี่ยนแปลง 9 คำ และคงเสียงเดิม 1 คำ ด้านความหมาย มีทั้งความหมายกว้างออก 9 คำ ความหมายย้ายที่ 1 คำ แต่ไม่พบความหมายแคบเข้า และความหมายคงเดิม Abstract The purpose of this analysis was to analyze study of modify the word, sound and meaning of Sanskrit in Thai. The example from both languages 10 each total 20 words by drawing for analysis form of foreign language for interest people. To comparative the Royal Institute dictionary 1999 with Pali - Thai-English Dictionary issue by Her Royal Highness Princess, Princess of Phrachanburinareunat. The results of the study were as follows: 1. When we use the Pali language in Thai language have to keep original in to 3 words, to change or added in to 7 words, also 6 sounds of both language have to change in to 4 words, the wide meaning has 8 words, the moving meaning got 2 words but don’t found it out of narrow meaning and the source meaning. 2. To analyze study about the change of Sanskrit language, when we apply to Thai language have to keep original in 1 word and change the vocable in 9 words. The sound in Sanskrit and Thai have to change in 9 vocals and keep the original one in 1 vocal. We found it out of the wide meaning in 9 words and the moving meaning was 1 word, but not for narrow meaning and the source meaning in any place.